Mitigation strategies for anti‐D alloimmunization by platelet transfusion in haematopoietic stem cell transplant patients: a survey of NCCN® centres. Issue 4 (20th February 2020) - Poston, Jacqueline N.; Sugalski, Jessica; Gernsheimer, Terry B.; Marc Stewart, F.; Pagano, Monica B.
Abstract : Background and objectives: D‐negative patients are at risk of developing an alloantibody to D (anti‐D) if exposed to D during transfusion. The presence of anti‐D can lead to haemolytic transfusion reactions and haemolytic disease of the newborn. Anti‐D alloimmunization can also complicate allogeneic haematopoietic stem cell transplantation (HSCT) with haemolysis and increased transfusion requirements. The goal of this study was to determine whether cancer centres have transfusion practices intended to prevent anti‐D alloimmunization with special attention in patients considered for HSCT. Methods and materials: To understand transfusion practices regarding D‐positive platelets in D‐negative patients with large transfusion needs, we surveyed the 28 cancer centres that are members of the National Comprehensive Cancer Network ® (NCCN ® ). Results: Nineteen centres responded (68%). Most centres (79%) avoid transfusing D‐positive platelets to RhD‐negative patients when possible. Four centres (21%) avoid D‐positive platelets only in D‐negative women of childbearing age. If a D‐negative patient receives a D‐positive platelet transfusion, 53% of centres would consider treating with Rh immune globulin (RhIg) to prevent alloimmunization in women of childbearing age. Only one centre also gives RhIg to all D‐negative patients who are HSCT candidates including adult men and women of no childbearing age. Conclusion: There is wide variation in platelet transfusion practices for supporting D‐negative patients. The majority of centres do not have D‐positive platelet transfusion policies focused on preventing anti‐D alloimmunization specifically in patients undergoing HSCT. Multicentre, longitudinal studies are needed to understand the clinical implications of anti‐D alloimmunization in HSCT patients.